Simulating the Cascading Effects of an Extreme Agricultural Production Shock: Global Implications of a Contemporary US Dust Bowl Event - Heslin, Alison; Puma, Michael J.; Marchand, Philippe; Carr, Joel A.; Dell'Angelo, Jampel; D'Odorico, Paolo; Gephart, Jessica A.; Kummu, Matti; Porkka, Miina; Rulli, Maria Cristina; Seekell, David A.; Suweis, Samir; et al. (Frontiers in Sustainable Food Systems, 2020)
Higher temperatures expected by mid-century increase the risk of shocks to crop production, while the interconnected nature of the current global food system functions to spread the impact of localized production shocks throughout the world. In this study, we analyze the global potential impact of a present-day event of equivalent magnitude to the US Dust Bowl, modeling the ways in which a sudden decline in US wheat production could cascade through the global network of agricultural trade. We use observations of country-level production, reserves, and trade data in a Food Shock Cascade model to explore trade adjustments and country-level inventory changes in response to a major, multi-year production decline. We find that a 4-year decline in wheat production of the same proportional magnitude as occurred during the Dust Bowl greatly reduces both wheat supply and reserves in the US and propagates through the global trade network. By year four of the event, US wheat exports fall from 90.5 trillion kcals before the drought to 48-52 trillion kcals and the US exhausts 94% of its reserves. As a result of reduced US exports, other countries meet their needs by leveraging their own reserves, leading to a 31% decline in wheat reserves globally. These findings demonstrate that an extreme production decline would lead to substantial supply shortfalls in both the US and in other countries, where impacts outside the US strongly depend on a country’s reserves and on its relative position in the global trade network.